Probiotics and Oral Health - Haukioja, Anna (Dental Investigations Society, 2010)
The number of products containing probiotics, viable bacteria with proven health benefits, entering the market is increasing. Traditionally, probiotics have been associated with gut health, and most clinical interest has been focused on their use for prevention or treatment of gastrointestinal infections and diseases; however, during the last decade several investigators have also suggested the use of probiotics for oral health purposes. The aim of this review is to examine potential mechanisms of probiotic bacteria in the oral cavity and summarize observed effects of probiotics with respect to oral health. The review focuses on probiotic lactobacilli and bifidobacteria, genera that are most used in various probiotic products.